Why children of college graduates outperform their schoolmates. A study of cousins and adoptees - Torbjørn Hægeland; Lars Johannessen Kirkebøen; Oddbjørn Raaum; Kjell G. Salvanes (Statistics Norway, Research Department, 2010)
There is massive cross-sectional evidence that children of more educated parents outperform their schoolmates on tests, grade repetition and in educational attainment. However, evidence for causal interpretation of this association is weak. Within a rich census level data set for Norway, we examine the causal relationship using two approaches for identification: cousins with twin parents and adopted children. In line with most of the literature, we find no effect of mothers' education on children's school performance using the children-of-twins approach. However, for adopted children, mother's education has a positive effect, but only a third of the size of the effect found in biological relationships in adopting families. Carefully tracking the work experience of parents during offspring childhood, we find no support for the hypothesis that the small causal effects of parental education can be explained by detrimental effects of higher labour force participation among more educated mothers.
Keywords: I21; J24; J62; 330; Intergenerational transmission; education; pupil achievement